2022
DOI: 10.1002/jum.16089
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Ultrasound Parameters for the Differential Diagnosis of Malignant and Benign Peripheral Nerve Sheath Tumors

Abstract: Objectives The objectives were to identify the key features of malignant and benign peripheral nerve sheath tumors (PNSTs) and determine a strategy for differentiating them using sonography. Methods Forty‐six malignant peripheral nerve sheath tumors (MPNSTs) and 83 benign peripheral nerve sheath tumors (BPNSTs) confirmed by pathology from April 2010 to July 2021 were included. The general data and grayscale and color Doppler ultrasonic manifestations were compared between the two groups. We used single factor,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
6
0
2
Order By: Relevance
“…A previous study assessing dynamic contrast-enhanced MRI reported that early arterial enhancement was significantly more frequent in MPNSTs than in benign peripheral nerve sheath tumors (BPNSTs; 50% [4 of 8] vs 11% [2 of 18], P = 0.03) 8 . Another study assessing ultrasonography reported that hypervascularity was more frequently observed in MPNSTs than in BPNSTs (89% [41 of 46] vs 59% [49 of 83], P = 0.03) 9 . However, no study has compared the vascularity between low-grade and high-grade MPNSTs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study assessing dynamic contrast-enhanced MRI reported that early arterial enhancement was significantly more frequent in MPNSTs than in benign peripheral nerve sheath tumors (BPNSTs; 50% [4 of 8] vs 11% [2 of 18], P = 0.03) 8 . Another study assessing ultrasonography reported that hypervascularity was more frequently observed in MPNSTs than in BPNSTs (89% [41 of 46] vs 59% [49 of 83], P = 0.03) 9 . However, no study has compared the vascularity between low-grade and high-grade MPNSTs.…”
Section: Discussionmentioning
confidence: 99%
“…8 Another study assessing ultrasonography reported that hypervascularity was more frequently observed in MPNSTs than in BPNSTs (89% [41 of 46] vs 59% [49 of 83], P = 0.03). 9 However, no study has compared the vascularity between low-grade and high-grade MPNSTs. Although dynamic contrast-enhanced MRI was not evaluated in the present study, our results might suggest that high-grade MPNSTs have a hypervascular nature compared with low-grade MPNSTs.…”
Section: Discussionmentioning
confidence: 99%
“…These features result in misdiagnosis as cystic lesions. 7 The "rat tail sign" is the most specific characteristic in diagnosing neurogenic tumors on ultrasound. It can be recognized easily when the tumor occurs in large nerve.…”
Section: Discussionmentioning
confidence: 99%
“…On ultrasound, most NLCNs presented as fusiform (27/43, 62.8%), well‐defined (42/43, 97.7%), encapsulated (39/43, 90.7%), anechoic (34/43, 79.1%), homogeneous lesion (39/43, 90.7%) with enhancement of posterior echo (29/43, 67.4%), and avascularity (37/43, 86.0%). These features result in misdiagnosis as cystic lesions 7 …”
Section: Discussionmentioning
confidence: 99%
“…MRI remains the preferred imaging method for evaluating the tumor site, lesion degree, and growth, 11 but it is expensive, time‐consuming, and has contraindications. Different MRI findings of MPNSTs and the diagnostic efficacy of MRI in differentiating MPNSTs and BPNSTs 1,12 have been previously reported; however, few studies have reported the ultrasonic parameters of MPNSTs and BPNSTs and constructed a practical scoring system to distinguish them 13,14 . Additionally, studies reporting the diagnostic efficacy of a combination of clinical and ultrasound features with MRI are still scarce.…”
mentioning
confidence: 99%